1996
DOI: 10.1109/22.539945
|View full text |Cite
|
Sign up to set email alerts
|

The dependence of EM energy absorption upon human head modeling at 900 MHz

Abstract: Abstruct-In this papier the dependence of electromagnetic energy absorption at 900 IMHz in the human head on its anatomy and its modeling are investigated for RF-sources operating in the very close proximity of the head. Different numerical head phantoms based on MRI scans of three different adults were used with voxel sizes down to 1 mm:'. Simulations of the absorption were performed by distinguishing the electrical properties of up to 13 tissue types. In addition simulations with modified electric parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
0
7

Year Published

1999
1999
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(76 citation statements)
references
References 11 publications
5
64
0
7
Order By: Relevance
“…Similar results were derived with the same method in [19]. Moreover, in [20,21] the use of different configurations of the human head coupled to a dipole antenna, pointed out that the average spatial peak SAR values are slightly dependent on the shape, size or whether the phantom is homogeneous or not. The homogeneous representation of the human phantom is proposed in these studies, as it reduces the number of tests (due to the symmetry of the antenna that is observed at the direction parallel to the surface), without simultaneously overestimating the average spatial peak SAR values.…”
Section: Introductionsupporting
confidence: 68%
“…Similar results were derived with the same method in [19]. Moreover, in [20,21] the use of different configurations of the human head coupled to a dipole antenna, pointed out that the average spatial peak SAR values are slightly dependent on the shape, size or whether the phantom is homogeneous or not. The homogeneous representation of the human phantom is proposed in these studies, as it reduces the number of tests (due to the symmetry of the antenna that is observed at the direction parallel to the surface), without simultaneously overestimating the average spatial peak SAR values.…”
Section: Introductionsupporting
confidence: 68%
“…SAR is evaluated by two methods: one experimental and one analytical. In the experimental method, the electrical field in a liquid phantom is measured [19] or the temperature rise in a solid phantom is measured and commuted to SAR [20]. It is difficult, however, to correctly measure the temperature rise with these methods because there is not only a temperature increase in the phantom due to the electromagnetic field but also a temperature increase in the transcutaneous transformer due to copper loss.…”
Section: ) Estimation Of Sarmentioning
confidence: 99%
“…According to the working frequency, the antenna power, the power radiated by the antenna, the dielectric properties of tissues, the distance between the antenna and the head gives a look of reflection coefficient, a SAR value (between 10 and 1 g), the value of radiation efficiency, the value of the input power, the input impedance. So from this explanation, we have took as input the reflection coefficient of the antenna, the working frequency, the distance d between the antenna and the body, the input power, the output power, the permittivity of fabric, the fabric density and the conductivity of tissue and as an output they obtained the reflection coefficient, the SAR values averaged over 10 and 1 g (Hombach et al, 1996;Okoniewski and Stuchly, 1996;Kouveliotis and Panagiotou, 2006;Sager et al, 2003), the radiation efficiency, the power absorbed and the input impedance. Figure 3 shows the Neural model applied to the interaction.…”
Section: Modellingmentioning
confidence: 99%